Scaling genetic resources: New paradigms for diagnosis and treatment of rare genetic disease. Issue 1 (30th November 2022) - Vockley, Jerry; Defay, Thomas; Goldenberg, Aaron J.; Gaviglio, Amy M.
Abstract: Development of genetic tests for rare genetic diseases has traditionally focused on individual diseases. Similarly, development of new therapies occurred one disease at a time. With >10, 000 rare genetic diseases, this approach is not feasible. Diagnosis of genetic disorders has already transcended old paradigms as whole exome and genome sequencing have allowed expedient interrogation of all relevant genes in a single test. The growth of newborn screening has allowed identification of diseases in presymptomatic babies. Similarly, the ability to develop therapies is rapidly expanding due to technologies that leverage platform technology that address multiple diseases. However, movement from the basic science laboratory to clinical trials is still hampered by a regulatory system rooted in traditional trial design, requiring a fresh assessment of safe ways to obtain approval for new drugs. Ultimately, the number of nucleic acid‐based therapies will challenge the ability of clinics focused on rare diseases to deliver them safely with appropriate evaluation and long‐term follow‐up. This manuscript summarizes discussions arising from a recent National Institutes of Health conference on nucleic acid therapy, with a focus on scaling technologies for diagnosis of rare disorders and provision of therapies across the age and disease spectrum. Abstract : Scaling technologies for diagnosis and treatment of rare genetic disorders will take a coordinated effort across many disciplines to deliver therapies equitably and efficiently.